Molecular and Metabolic Pathogenesis of Familial Combined Hyperlipidemia and Association with Metabolic Syndrome - Sikandar Hayat Khan (Journal of Glycomics And Metabolism, 2019)
Background The objective of this review is to unify the various genetic defects along with elaborating metabolic pathways in Familial Combined Hyperlipidemia(FCHL) and also to differentiate the phenotype of FCHL from metabolic syndrome. Methods PubMed and Cochrane’s library was searched for keyword “Familial combined hyperlipidemia” and latter with “Familial combined hyperlipidemia genes” to finally shortlist 23 articles. Further search with key words “molecular pathogenesis of familial combined hyperlipidemia” and “metabolic syndrome and familial combined hyperlipidemia” was carried out for finding molecular defects in FCHL, non-molecular findings distinguishing FCHL from metabolic syndrome and overlapping features between FCHL and metabolic syndrome. Results Major culprit regions identified included Chromosome-1q21-q24(USF1 and FOXA2) , Ch-11q (APOA5), Ch-16q24, Ch-20q12-q13.1, Ch.4q32.3 (rs6829588), and Ch-19q13.32 containing PVRL-2 gene (Also known as Nectin-2). The genetic and metabolic pathways linked to FCHL may involve: 1-Defective clearance of Apo-B containing lipoproteins, 2-Overproduction of Apo-B containing lipoprotein i.e., VLDL and 3-Adipose tissue dysfunction. FCHL phenotype showed close resemblance with metabolic syndrome clinical and biochemical features with slight differences. Conclusion The reviewed data suggested that FCHL phenotype is the resultant end outcome from multiple molecular defects and thus underlying genetic defect identification in the index case is important for personalized medicine and incoming gene therapy. Further research is warranted to explore specific genetic defects.
Keywords: familial combined hyperlipidemia (FCHL)